Preparation and application of polyaldehyde trehalose as a new hydrophilic anti-crease finishing agent for cotton fabric. Issue 3 (February 2021) - Lou, Jiangfei; Yuan, Jiugang; Wang, Qiang; Wang, Ping; Xu, Jin; Yu, Yuanyuan; Fan, Xuerong
Polyaldehyde trehalose (OTr) was prepared and applied to cotton fabric as an anti-crease finishing agent under Lewis acid conditions. OTr contains reactive groups (aldehyde groups) and hydrophilic groups (hydroxyl groups). After the aldehyde groups crosslink with the hydroxyl groups of the fibers, the hydroxyl groups of the OTr improve the hydrophilicity of the finished fabric. The target product was characterized by Fourier transform infrared spectroscopy and proton nuclear magnetic resonance. The optimum process conditions for anti-crease finishing were studied. The optimal anti-crease finishing process for OTr was 10.0%, a MgCl2 concentration of 2.0%, a pH of 3, and curing for 3 min at 150℃. The efficiency of the OTr-treated cotton fabrics was examined, and the anti-crease property, whiteness, tensile strength, hydrophilicity, and staining property of the OTr and conventional anti-crease finishing reagents were compared. The anti-crease property, whiteness, and tensile strength of the OTr-treated fabric improved significantly, but were lower than those of the butane tetracarboxylic acid and glutaraldehyde. Fabric that was treated with the new prepared agent presented a satisfactory hydrophilicity, which indicates that OTr can be used as an effective hydrophilic crosslinking agent.